PENGEMBANGAN MEDIA PEMBELAJARAN KARTU DOMINO UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA KELAS VI DI SDN BOJONGMANGU 01 - Santika, Dewi; Ira Restu Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the lack of learning media which resulted in low understanding of concepts. This research aims to increase understanding of science concepts for class VI SDN Bojongmangu 01. The research used is Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, evaluation. The results show that the domino card media was declared